2021
DOI: 10.3390/biology10111179
|View full text |Cite
|
Sign up to set email alerts
|

The BPH/5 Mouse Model of Superimposed Preeclampsia Is Not a Model of HELLP Syndrome

Abstract: Preeclampsia (PE) is a multisystemic disease of pregnancy affecting 2–8% of women worldwide. PE-induced liver disease is a rare but important complication of pregnancy. The pathogenesis of liver dysfunction in PE is poorly understood, but is correlated with dysregulated angiogenic, inflammatory, and hypoxic events in the early phase of placental development. Because BPH/5 mice develop the maternal and fetal hallmarks of PE during pregnancy, we hypothesized that they may also share the clinicopathologic finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Disruption of normal placental development and smaller fetal weight at birth suggests that this model may be similar to early-onset preeclampsia with fetal growth restriction ( Waker et al, 2021 ). Recent studies; however, have changed the context of the BPH/5 model and expanded the comorbidity beyond spontaneous chronic borderline hypertension and to now include preexisting metabolic disease, obesity, and fatty liver disease ( Sutton et al, 2017 ; Reijnders et al, 2019 ; Johnston et al, 2021 ; Sones et al, 2021 ).…”
Section: Mouse Models With Multiple Comorbiditesmentioning
confidence: 99%
“…Disruption of normal placental development and smaller fetal weight at birth suggests that this model may be similar to early-onset preeclampsia with fetal growth restriction ( Waker et al, 2021 ). Recent studies; however, have changed the context of the BPH/5 model and expanded the comorbidity beyond spontaneous chronic borderline hypertension and to now include preexisting metabolic disease, obesity, and fatty liver disease ( Sutton et al, 2017 ; Reijnders et al, 2019 ; Johnston et al, 2021 ; Sones et al, 2021 ).…”
Section: Mouse Models With Multiple Comorbiditesmentioning
confidence: 99%
“…Likewise, references indicated that CXCL2 is upregulated in PE patients and the blood pressure high/5 (BPH/5) female mouse model of PE ( Yan et al, 2013 ; Batts et al, 2021 ). Interestingly, Johnston and others ( Johnston et al, 2021 ) observed that CXCL2 mRNA expression was considerably lower in PE hepatic transaminases low platelets (HELLP) mouse model syndrome. The decreasing trend of CXCL2 during late pregnancy is unknown.…”
Section: Role Of CXC Chemokines In the Pathogenesis Of Pementioning
confidence: 99%
“…However, BPH/5 mice do not develop features of severe disease, such as HELLP syndrome. 69 Many groups have attempted to study the mechanisms of why this strain develops preeclampsia-like states. Sones et al 70 have suggested that antiangiogenic sFLT1 protein was upregulated in the BPH/5 placentas and that aberrant sFLT1 expression was responsible for the complement activation and poor placentation in this model.…”
Section: Disease Models Of Cardiovascular Complications Of Pregnancymentioning
confidence: 99%